Stochastic resin transfer molding process - Park, M.; Tretyakov, M.V. (Society for Industrial and Applied Mathematics, 2017)
We consider one-dimensional and two-dimensional models of the stochastic resin transfer molding process, which are formulated as random moving boundary problems. We study their properties, analytically in the one-dimensional case and numerically in the two-dimensional case. We show how variability of time to fill depends on correlation lengths and smoothness of a random permeability field.